Penentuan Lokasi TPA dengan Pendekatan Spasial di Pulau Kecil Kota Makassar - Agus Bintara Birawida; Bukroanah Amir Makkau; Indra Dwinata (Faculty of Public Health, Hasanuddin University, Makassar, 2018)
Solid waste is an environmental issue that currently still occurs in the islands, especially for small islands.Every year waste disposed into the sea continues to experience levels caused by community activities around theisland. The aimof the research is to determine the best point in the location of the Final Waste Disposal Site (TPA).This research uses descriptive method with spatial approach. Retrieval of data to determine locations in GPS locationand measurement in the field. The results showed that the GPS coordinate points and the objectives of themeasurement purposes, namely the slope of the slope, the distance between the coast and land, the land function,including the air of the ground, and the capacity of the available land for locations on Kodingareng Lompo Islandlatitude 119.26514o and longitude of -5.14793o placed in the center of the island. Sanitary landfill is the most suitabletype of landfill to be applied on Kodingareng Lompo Island.